The Effectiveness of Training and Development On Employee Performance to Enhance Competitive Advantage: A Case Study of Social Enterprise Development Sierra Leone (Send-Sl) - Alhadji Musa Kamara; Widayat; Bambang Widagdo (Universitas muhammadiyah malang, 2022)
This study aimed to examine the effect of Human Resources development and training on performance. Data were collected using questionnaires from 71 workers who were selected at random. The collected data were analyzed using Structural Equation Modeling (SEM), which employed Smart-PLS3. The analysis results show that on-the-job training measured by (Job- rotation, Job-instruction, orientation and workshop) had no significant direct effect on Employee Performance but a significant direct effect on Employee Competitive Advantage. While Off-the- job training measured by (exchange learning, short courses, self-development, and simulation) had a significant direct impact on employee performance but had no significant immediate effect on employee competitive advantage. Also, employee performance was found to have a significant direct impact on employee competitive advantage. The result further revealed that through the mediation of employee performance, on-the-job training had no significant indirect effect on employee competitive advantage, while off-the-job training had a substantial indirect impact on employee competitive advantage.